Morphofunctional changes of microglia in adult and old Wistar rats - A. V. Sentyabreva; E. A. Melnikova; E. A. Miroshnichenko; I. S. Tsvetkov; A. M. Kosyreva (Медицинская иммунология, 2023)
Alzheimer's disease (AD) is one of the most prevalent neurodegenerative diseases leading to dementia. There is no effective treatments for this disease so far, as well as a consensus concerning the mechanisms of its pathogenesis initiation. Obtaining data on them in vivo is possible only by modeling neurodegeneration in laboratory animals. Alzheimer’s disease (AD) is one of the most prevalent neurodegenerative diseases leading to dementia. There is no effective treatments for this disease so far, as well as a consensus concerning the mechanisms of its pathogenesis initiation. Obtaining data on them in vivo is possible only by modeling neurodegeneration in laboratory animals. Among the various theories of the initiation of neurodegeneration, the impact of microglia is vigorously studied recently, as well as inflammaging, which is a term for chronic age-related low-grade systemic inflammation. It manifests in the increasing number of senescent cells with senescence-associated secretory phenotype (SASP). Eventually, it leads to manifestation and progression of age-related diseases, such as AD. The aim of the study was to evaluate age-related changes in microglia, pro- and anti-inflammatory cytokines expression levels in the brain, as well as ones of microglial activation, and also subpopulations of lymphocytes in peripheral blood. We used male Wistar rats of two age groups, which were composed of old (age 24 months) and adult (age 3 months) rodents, without any additional exposure. In the hippocampus, morphological changes in microglia were assessed on preparations stained with antibodies to Iba1. In the prefrontal cortex, RT-qPCR was used to study the level of expression of pro-inflammatory IL-6 and TNFa, anti-inflammatory IL-10 and TGF-b cytokines, as well as microglial activation markers iNOS and MMP-9. In the peripheral blood, the relative numbers of the main subpopulations of lymphocytes and monocyte were measured by flow cytometry. It was shown that, compared with adult rats, old animals are characterized by significant changes in the morphology of microglia, an increase in the level of expression of pro-inflammatory and a decrease in anti-inflammatory cytokines, and an increase in microglia activation markers. With aging, a decrease in the percentage of monocytes and B cells in peripheral blood was observed. These data indicate the development of inflammaging, which displays itself in microglia activation, a shift in the balance of cytokine production towards pro-inflammatory ones, and, as a result, activation of the migration of monocytes and B lymphocytes from the blood into tissues. Thus, it is justified to study the role of inflammation in the development of AD in old animals whose physiological state corresponds to that in humans. Further research in this area will expand the understanding of the mechanisms of initiation and progression of neurodegeneration, which is necessary for the development of novel and effective therapeutic approaches to the treatment of AD.